PENGEMBANGAN MEDIA PENYAMPAIAN INFORMASI DAN PROMOSI PADA PT KOTA JATI FURINDO JEPARA - Irawan Adi Wibowo (STEKOM PRESS, 2016)
PT Kota Jati Furindo is a private company engaged in furniture especially outdoor and indoor furniture and has been established since 1987, having its address at Jl. Raya Jepara - Bangsri Km. 6.5 Jepara, originated from a company that makes products based only on orders, prioritizing high quality product quality. In mid-2008 there was a financial crisis that hit countries in Europe which then affected orders for furniture products from companies. In early 2009 PT Kota Jati Furindo created a website aimed at promoting and introducing products throughout the world, the website creation target was for the export market or overseas, therefore the website used an international language, English. In early 2013 the company began to look for consumers from within the country so that the sustainability of the business can run well. Efforts made by companies to get consumers in the country began with introducing their products to the public, it was done because there are still many people in Indonesia who are not familiar with furniture products from PT Kota Jati Furindo, to support the efforts of the company needed a promotional media that is in accordance with current company needs. Based on the above problems, it is necessary to make a promotional media at PT. Kota Jati Furindo to facilitate consumers and of course increase company sales in the form of catalogs, brochures, wall clocks, t-shirts and mugs. Therefore the writer will make a study entitled Development of Information Submission and Promotion Media at PT Kota Jati Furindo Jepara